Eating disorders: Involvement of pediatricians in their prevention, early detection, evaluation and multidisciplinary management - Raquel Jiménez García; Covadonga Canga-Espina; Andrea Múñoz Domenjó; Gemma Ochando Perales; Azucena Díez-Suárez (Anales de Pediatría (English Edition))
Eating disorders are severe mental health disorders characterized by changes in eating-related behavior, thoughts and emotions. They typically manifest at young ages, chiefly in adolescence or preadolescence. Due to their complexity, the management of eating disorders requires a multidisciplinary approach led by mental health professionals. However, the high demand for services may delay access to specialized care, which makes it necessary for pediatricians to adopt a proactive role.Pediatricians play a key role in the prevention of eating disorders by promoting a healthy relationship with food and body image as well as in their detection and initial management, enabling the implementation of early interventions to stabilize the patient while coordinating specialized care. The pediatrician is also a key figure throughout the followup in monitoring the physical and mental health of affected patients, guaranteeing the delivery of comprehensive care in collaboration with the multidisciplinary team. Resumen: Los Trastornos de la Conducta Alimentaria (TCA) son enfermedades mentales graves caracterizadas por alteraciones en el comportamiento, los pensamientos y las emociones relacionadas con la ingesta de alimentos. Suelen manifestarse a edades tempranas, principalmente en la adolescencia o preadolescencia. Su complejidad requiere un abordaje interdisciplinar, liderado por profesionales de la salud mental. No obstante, la alta demanda asistencial puede retrasar el acceso a la atención especializada, lo que hace imprescindible que el pediatra asuma un rol proactivo.Su papel es clave en la prevención, promoviendo una relación saludable con la alimentación y la imagen corporal, así como en la detección y manejo inicial, asegurando intervenciones tempranas que estabilicen al paciente mientras se coordina la atención especializada. Además, a lo largo de toda la evolución de la enfermedad, el pediatra desempeña una función fundamental en el seguimiento del estado de salud física y mental, garantizando una atención integral en colaboración con el equipo interdisciplinar.